O distinctivo de uma alma bem formada: princípios geraes de moral no manual enciclopédico para uso das escolas de instrucção primária (1862-1874) - Araújo, Camila Almeida de (2022)
The present work intends to understand the principles of morality laid out in the Encyclopedic Manual, as contributions to the formation of youth. The principle of morality was somewhat intrinsic to imperial society since it was tied to the foundation of the Brazilian people. The work, containing 700 pages, has an encyclopedic character, as described by its nomenclature, by joining the contents involving all sorts of subjects corresponding to primary education. The research is part of a moment of renewal of historiography, a context in which new sources and new research objects get to be considered relevant, such as the press and, in turn, newspapers and books. Among the theorists who lent us support, we highlight Chartier’s studies (1999) – the history of the book and the study of practices-, Durkheim (1983,1999,1952) – the concept of collective morals and social fact -, and Foucault (2008) – the control of bodies. The relevance of the theme is based on the possibility of understanding the imperial society in its various instances, starting from the knowledge produced or disseminated by it, in this case, the Manual, as well as the absence of works that deal directly with our object, namely: the principles of morality in the Encyclopedic Manual. The type of research we carry out is historical research, which constitutes a branch of documentary research. We recognize the magnitude of the work and its relevance to the instruction and society of the time, due to the extent of the contents, questions, and explanations. Therefore, although the Encyclopedic Manual had its contributions to youth signed in a moralizing discourse, revealing what an ideal society should be, it did not mean that all people would be submissive to their dictates, due to the diversity of provinces that had access to the Manual.